Artificial intelligence research and development - Angulo, Cecilio; Godo, L. (Lluís) (Frontiers in artificial intelligence and applications, 2007)
Contains papers which were presented at the 10th anniversary of the International Conference of the ACIA (CCIA'07) in Sant Julia de Loria (Andorra), October 25-26th, 2007. This book is intended for those computer scientists or engineers who are interested in artificial intelligence.